Islam dan Egalitarianisme: Ruang Terbuka Kesetaraan Gender - Itmam Aulia Rakhman (Lembaga Penelitian, Penerbitan, dan Pengabdian Masyarakat (LP3M) Institut Agama Islam Bakti Negara (IBN) Tegal, 2019)
Islam is a religion that inherently carries the spirit of egalitarianism. The facts about the variants of Islam that are central, formal and pure are egalitarian and scientific - while the hierarchy and existence are developing peripheral forms - help them adjust to the modern world. As a religion that carries an egalitarian spirit, Islam should put its people in various social issues - and of course religion - equally, without distinguishing between rich and poor, old and young, male and female. Because the